PEMBANGUNAN MODEL DATA UNTUK SISFO AKADEMIK STIKOM DINAMIKA BANGSA JAMBI - Ali Sadikin (Jurnal PROCESSOR, 2017)
SISFO Akademik STIKOM Dinamika Bangsa Jambi was builded with supported by not good database design. It’s caused by the information need was responsed by building database incidentially without data model which can be used as a guide. The results are as like the lost of historical data, hard to make important information and difficult to integrating it with another information system. To fix those problems then needed to do a study to build a data model which can describe the academy domain activities which result of the analysis of it’s business process. In the building of the data model for SISFO Akademik STIKOM Dinamika Bangsa Jambi is parted in first two steps which are the conceptual and the logical step. For the data model result representation, ER diagram is used. So that with the data model, SISFO Akademik STIKOM Dinamika Bangsa Jambi could supported by a better integrated and better integrity database.